NTEGRAL AND DIFFERENTIAL FEATURES OF TAUTOLOGY AND PLEONASM (Scientific journal of the Fergana State University, 2024)
This study is aimed at analyzing and classifying the main characteristics (signs) of tautology and pleonasm in the modern Russian language. The study is based on the study of the main theories and approaches to understanding lexical redundancy proposed by Russian linguists, as well as on the analysis and classification of modern language material. The study of the origin of terms corresponding to the characteristics of tautology and pleonasm, and their distribution at different levels of language, gives grounds for the conclusion that in the modern Russian language tautology and pleonasm are separate phenomena.